Phylogeography of Equine Infectious Anemia Virus - Jara, Manuel; Frias-De-Diego, Alba; Machado, Gustavo (Frontiers in Ecology and Evolution, 2020)
Equine Infectious Anemia virus (EIAV) is the causative agent of one of the most impacting infectious diseases affecting equids. EIAV is genetically diverse with several lineages circulating globally. To elucidate EIAV global spread patterns, we studied its spatiotemporal dynamics applying Bayesian phylodynamic analyses, using a worldwide compiled dataset composed of unique sequences of the gag gene. In addition, we performed a scoping review of 1.470 publications on EIAV to characterize the spatiotemporal trends in EAIV research. Phylogeographic reconstruction suggested Hungary as the most likely country of origin for current EIAV circulation (root state posterior probability = 0.21), and one of the most important centers of diversification for the disease. Historical EIAV spread was predominantly characterized by long-distance spread across continents. As a result, we found that the American and Asian circulating EIAV (i.e., Mongolia) are more related to European lineages than to other Asian countries, being Europe the continent with the highest EIAV phylogenetic diversity. Our bibliometric analysis showed a continuous increment in the number of publications per year, where the United States and China appeared as the countries with highest EIAV-related scientific production. This study provides a historical geographic mapping of the EIAV linages’ spread patterns. In addition, we identified important asymmetry between the current research effort and the availability of genetic data which restricted our abilities to quantify for example the time frame of virus dispersal.